Determinants of housing prise:Evidence from panel data - Ismail, Nur Hafizah; Nayan, Sabri
Housing industry plays a vital role to a colmtry's economy, however, increase in house prices could contribute to negative growth of economic and financial perfomce. It is cmcial to study the determinants of house price in order to control the price volatility and to reduce the risk of potential repeated financial orisis. This paper investigates the determinants of housing prices in, selected East-Asian cbuntries: Malaysia, Singapore, Indonesia and Thailand by using pooled mean regression, over a quarterly data fiom 2000 to 2010. The key faators investigabd were GDP, bank lending rate, wtemploymenl rate and stock price index. AU determinants were found tw be significantly related to the crosscountry House Price Index @PI). East-Asian countries should adapt r e t e r n imperative action to wnhal house prices from escalating and to avoid financial instability due to housing bubble fium happen.